Little red riding hood: khizer readers bilingual english & urdu stories (Khizer readers Lahore, 2020)
**Little Red Riding Hood: Khizer Readers Bilingual English & Urdu Stories** is a bilingual children's book that retells the classic fairy tale. It introduces young readers to both English and Urdu languages while captivating them with the timeless story of a girl who encounters a cunning wolf on her way to visit her grandmother. The book uses simple language and vibrant illustrations to make learning fun and engaging.